Physiographic study of Shatt Al-Arab Delta South of Iraq by Application of Remote Sensing Technique - Albadran, B.N.; Al-Mulla, S.T.; Abd-Alqader, M.M. (Mesopotamian Journal of Marine Sciences, 2022)
The Shatt Al-Arab River is formed by the confluence of the Tigris and Euphrates Rivers near Qurna 75 km, Basrah Governorate, approximately 75 km north of the city of Basrah, southern of Iraq. Satellite images of Landsat 7 ETM+ for years 2000, 2002 and 2006 were processed with ERDAS Imagine 8.4 and ArcGIS 9.3. They were used to interpret the geomorphology of Shatt Al-Arab delta. Shuttle Topographic Radar Mission. Geomorphologic structures, suspended load distribution and lateral movement of the main channel are interpreted and three lobes are distinguished at the formative delta front, confirming lateral channel movement as the prime factor in the delta’s formation. A westward deviation in the main channel of the Shatt Al-Arab River could divert into Abdullah Creek within a few years.